Design and Implementation of a Modular Self-Reconfigurable Robot. (24th March 2014) - Qiao, Guifang; Song, Guangming; Wang, Weiguo; Zhang, Ying; Wang, Yali
This paper presents the design and implementation of a new modular self-reconfigurable robot. The single module has three joints and can perform rectilinear motion, lateral shift, lateral rolling, and rotation. A flexible pin-hole-based docking mechanism is designed for self-assembly. With the proposed infrared-sensor-based docking method, multiple modules can be self-assembled to form versatile configurations. The modules communicate with each other through ZigBee protocols. The locomotion planning and geometry analysis of the single module are presented in detail and the efficiency of the single module's mobility is also demonstrated by experimental results. In automatic docking experiments with two modules, the proposed method is shown to be able to achieve an average success rate of 78% within the effective region. The average time of the docking process is reduced to 75 s. The maximum velocity of the I-shaped robot is up to 3.6 cm/s and the maximum velocity of the X-shaped robot is 4.8 cm/s. The detach-dock method for I-to-X transformation planning is also verified. The ZigBee-based communication system can achieve 100% receiving rate at 55 ms transformation interval.